Constitutional Conflict between Tourism Development and Karst Area Protection in Gunung Kidul: Analysis of Article 33 of the 1945 Constitution of the Republic of Indonesia and the Principles of Sustainable Development - Ayik Christina Efata; Deny Deny (Dinasti Research, 2026)
Over the past decade, the tourism sector in the karst region of Gunung Kidul has experienced substantial growth, contributing significantly to local revenue generation and expanding employment opportunities for surrounding communities. Nevertheless, the rapid development of tourism infrastructure, land-use conversion, and intensive exploitation of karst landscapes have generated constitutional concerns related to the State’s obligation to safeguard environmental sustainability. Karst ecosystems perform essential ecological functions, including groundwater storage, hydrological regulation, and providing habitats for diverse biological species. Consequently, environmental degradation in these areas may result in long-term ecological consequences. This study aims to examine the tension between tourism-driven economic development and the protection of karst environments from the perspective of Article 33 of the 1945 Constitution of the Republic of Indonesia, as well as the principles of sustainable development. The research employs a socio-legal approach, combining normative analysis of statutory regulations with conceptual examination of the green constitution doctrine and sustainable development framework. The findings indicate that Article 33 of the 1945 Constitution not only emphasizes state control over natural resources for the prosperity of the people but also implicitly incorporates principles of environmental sustainability and ecological responsibility. Accordingly, tourism policies that disregard environmental carrying capacity and ecological limits within karst regions risk contradicting constitutional mandates. The integration of sustainable development principles into spatial planning policies and licensing mechanisms is therefore essential to ensure a balanced relationship between economic advancement and environmental preservation.